2014
DOI: 10.1016/j.sbspro.2014.05.077
|View full text |Cite
|
Sign up to set email alerts
|

Adjusting College Students’ Support Services to Students’ Type: Lithuania's Case

Abstract: The article presents research that was conducted in order to identify the relationship between the demand of student support services and the types of students in Lithuanian colleges. The research was carried out by using a web-based survey. Students from all state colleges in Lithuania (N = 487) took part in the research. The results revealed that first year students' orientation courses, language training and community feeling development activities are the most important support services for collegiate and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Research in this area has been scant and has only focused on when the student support system should be activated [68]. No research has shown that supports is t to the student's needs [15]. Figure 1 shows the search process and inclusion of papers in this review.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Research in this area has been scant and has only focused on when the student support system should be activated [68]. No research has shown that supports is t to the student's needs [15]. Figure 1 shows the search process and inclusion of papers in this review.…”
Section: Resultsmentioning
confidence: 99%
“…Student support services are de ned in two ways: academic and non-academic services. Academic services are performed by academic staff and are based on university decisions and are related to teaching and learning issues and problems However, non-academic services are not related to academic topics but they provide the Suitable conditions for the student [15,48,61]. Students' needs play an important role in designing and improving educational systems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, the concept and adoption of service quality has been prevalent in the higher education domain as universities are competing incessantly to acquire top achieving students (Green, 2014;Mmutle et al, 2017). Students are able to ascertain how reputable the academic support department is in supporting teaching and learning by the quality of services rendered (Tamuliené, 2013).…”
Section: The Role Of Academic Support Departments Toward University Smentioning
confidence: 99%